Social Rejection as Reflected in Happy Feet Film - Sidiq, Nuch Mochamad; Priyoto, Priyoto; Mujani, Sahril (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This study aims to know the social rejections and its triggers experienced by Mumble in the movie Happy Feet. The writer uses a qualitative method to conduct the data and theory. The result shows Mumble is ostracized and ridiculed by his peers because he cannot sing like the other penguins. The rejection from the community, which values conformity, leads to feelings of isolation and sadness for Mumble. Despite the sadness Mumble experiences, the film ultimately carries a positive message of self-acceptance, resilience, and the celebration of individuality. Mumble's journey is one of overcoming adversity and embracing his unique talents, turning what initially caused sadness into a source of strength and inspiration.